2021
DOI: 10.7150/ijbs.58857
|View full text |Cite
|
Sign up to set email alerts
|

Rac GTPase activating protein 1 promotes gallbladder cancer via binding DNA ligase 3 to reduce apoptosis

Abstract: Rac GTPase activating protein 1 (RACGAP1) has been characterized in the pathogenesis and progression of several malignancies, however, little is known regarding its role in the development of gallbladder cancer (GBC). This investigation seeks to describe the role of RACGAP1 and its associated molecular mechanisms in GBC. It was found that RACGAP1 was highly expressed in human GBC tissues, which was associated to poorer overall survival (OS). Gene knockdown of RACGAP1 hindered tumor cell proliferation and survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Elevated RACGAP1 expression has been recorded in various cancers, including hepatocellular carcinoma [ 23 ], basal-like breast cancer [ 24 ], and gallbladder cancer [ 25 ]. RACGAP1 stimulates STAT3 phosphorylation and promotes its nuclear translocation, thus facilitating cell proliferation, migration, and decreased chemosensitivity to doxorubicin in bladder cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RACGAP1 expression has been recorded in various cancers, including hepatocellular carcinoma [ 23 ], basal-like breast cancer [ 24 ], and gallbladder cancer [ 25 ]. RACGAP1 stimulates STAT3 phosphorylation and promotes its nuclear translocation, thus facilitating cell proliferation, migration, and decreased chemosensitivity to doxorubicin in bladder cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 The dilution of Trps1 antibody was 1:800. The IHC score was assessed according to previously established criteria [19][20][21][22] and independently evaluated by two experienced pathologists. In summary, the assessment of positive tumor cell proportion involved categorization: 0 represented ≤10% positive cells, 1 indicated ≤50% positive cells, 2 denoted ≤75% positive cells, and 3 signified ≥76% positive cells.…”
Section: Immunohistochemistry and Scoringmentioning
confidence: 99%
“…Abnormal expression of Rac GTPase activating protein 1 (RACGAP1) was involved in the pathogenesis and progression of plenty malignant tumors [ 9 , 10 ]. Previous research showed that overexpression of RACGAP1 promoted early HCC recurrence by clinical information collection and preliminary molecular experiment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%